Cancer Stem Cells from Tumor Cell Lines Activate the DNA Damage Response Pathway after Ionizing Radiation More Efficiently Than Noncancer Stem Cells - Heriberto Abraham Valencia-González; Graciela Ruíz; Elizabeth Ortiz-Sánchez; Alejandro García-Carrancá (Stem Cells International)
Recently, a subpopulation of tumor cells, called cancer stem cells (CSC), has been characterized, and these have emerged as a major topic in cancer research. CSC are proposed to repair DNA damage more efficiently than the rest of tumor cells, resisting chemotherapy or radiotherapy and causing clinical recurrence and metastasis. We aimed to determine the molecular basis of radioresistance and first compared the response to ionizing radiation (IR) between cancer stem cell-enriched cultures grown as spheres and conventional tumor cell line cultures grown as monolayer, from HeLa and MCF-7 cancer cell lines. To verify that our sphere cultures were enriched in CSC, we evaluated the double staining of CD49f and ALDH activity for HeLa cells by flow cytometry. We then evaluated whether differences could exist in sensor elements in the DNA damage response pathway among these cultures. We found that CSC cultures showed less sensitivity to radiation than conventional tumor cell line cultures. We observed a higher baseline expression of activated response sensor proteins of DNA damage, such as ATM, H2A.X, and PARP1, in untreated CSC cultures. These findings provide the first evidence, to our knowledge, that DNA damage response sensor proteins are present and preferentially activated in CSC, as opposed to the bulk of cells in monolayer cultures. Likewise, they provide the basis for biological differences in response to IR between CSC and other tumor cell populations. Understanding the DNA damage response pathway may provide therapeutic targets to sensitize CSC to cytotoxic therapies to improve current cancer treatments.